Institution Building of the Eurasian Economic Union: Challenges and Opportunities - ISKAKOVA, Zhanna Turkistanovna; BIMBETOV, Askhat Bolatbekovich; SARSENOVA, Saniya Nurzhanovna (Journal of Advanced Research in Law and Economics; Vol 7 No 4 (2016): JARLE, Volume VII, Issue 4(18), Summer 2016, 2016)
This article contains research of the structure and authorities of the institutional bodies of the Eurasian Economic Union and peculiarities of their institution building. In the course of the research we analyzed the Treaty on the Eurasian Economic Union, its annexes regulating the activities of the Supreme Council, the Eurasian Economic Commission and the Court of the Eurasian Economic Union. Article describes functional purpose of the institutional bodies mentioned above, their role in the activities of the Union, reviews the opinions of the Russian, Kazakh, Belorussian and foreign scientists on the supranational nature of the Union institutional bodies. The authors suggest the measures for improving the activities of the Eurasian Economic Union institutional bodies, including the legislative framework, governing their activities. The article also deals with the challenging issues connected with the integration of the Union members as well as the problems in the Union legislative system and the determination of the Union institutional bodies as the international organizations or supranational authorities. On the basis of scientific perspectives and provisions of the international contracts the authors develop their own point of view regarding it as well as precondition the opportunities of the institution building of the Union institutional bodies. The objective of the article is research of the system of the Eurasian Economic Union main bodies, their authorities and competences. In this research we applied the methods for analysis of international legal acts, juridical literature, the Mass Media as well as the general scientific methods, including cognitive and logical methods.